Women's marginalization from public spaces: The case of Aceh - Nor, M.R.M.; Inayatillah, A. (2011)
Women's roles and positions in the governmental system, as well as in other institutions in the contemporary context, can be seen from their involvement in the political arena and the ability of women to occupy decision-making positions. Women's inability to achieve important positions in public is influenced by many factors, including ideology and government policy, as well as by social changes and modernization. This article aims to focus on the condition of Acehnese women by analyzing their roles and positions in the governmental system as well as in other institutions. The discussion intends to explore the factors that have triggered the marginalization of Acehnese women in public. This article implies that the exclusion of Acehnese women from public spaces is largely caused by internal and external factors, by protracted conflicts as well as the modernization process in the region.